Innovating Sustainable Business Models: A Comparative Study of Indonesian Universities - Nurlia Fusfita; Marissa Putriana; Jamaluddin; Yetti Anita Sari; Nurlaila Adhani; Fadhl Mohammed Awadh Gharamah (Journal of Educational Studies, 2026)
This study aims to analyze and compare the dominant patterns of sustainable business model innovation in Legal Entity State Universities (PTNBH) and State Islamic Universities (UIN) in Indonesia. Using a qualitative comparative case study approach, this research analyzed public data from 12 PTNBH and 10 UIN, comprising annual reports, financial reports, and strategic documents, using MAXQDA 2022 software for systematic thematic analysis, incorporating open and axial coding stages, and validated through data triangulation. The findings reveal a significant dichotomy. PTNBH primarily developed Intellectual and Physical Asset Corporatization patterns, manifested through technology spin-offs, applied consulting, and commercial property development. This pattern reflects market logic and corporate efficiency, aiming to generate scalable non-tax revenue. Conversely, UIN frequently implemented Sharia-Based Socio-Economic Ecosystem Empowerment patterns, focusing on the development of Baitul Maal wat Tamwil (BMT), sharia cooperatives, community halal businesses, and religious consultancy services. This pattern is rooted in community logic and Islamic values, where economic activities serve as instruments for da’wah and community resilience. The study concludes that business model innovation patterns are determined by institutional fit with the logic, identity, and specific resources of each institution. Impliedly, no single universal business model is superior. The research recommends that policies supporting the financial independence of higher education institutions should respect these diverse pathways rather than applying a uniform approach.